Role of Human Capital in Digitalised & Sustainability-Oriented Supply Chains - Shirbhayye, Chandan (Digital Repository of Theses - SSBM Geneva, 2025)
Research Purpose: The objective of this study is to investigate the relationship between supply chains, human capital management, and to show how human capital management functions in supply chains that are digital and sustainability focused. It aims to understand how digital transformation in supply chains is influenced by human capital and how this digitalization can contribute to or hinder sustainability efforts. Methodology: This study was based on a mixed method (Including both qualitative and quantitative data collection) approach. For the purpose of quantitative data collection, primary data collection technique was used, including a questionnaire survey of 330 respondents. On the other hand, the qualitative data was collected through existing literatures, books, journal articles etc. Collected quantitative data was analysed using SPSS (Statistical Packages for Social Sciences) software, employing various statistical techniques such as correlation and regression. Results: The findings indicated that human capital plays a critical role in the successful integration of digital technologies within supply chains. Digital literacy and employee engagement were found to be significant factors in enhancing digitalization efforts, leading to improved supply chain efficiency and resilience. Additionally, the study revealed that digitalization and sustainability are increasingly interconnected, with digital tools offering both opportunities for more sustainable operations and challenges, such as increased energy consumption. Conclusions: The study establishes that digitisation of supply chain requires and unlocks competitive advantage and sustainability when supported by robust human capital management. This is because every industry has factors that define it and makes it different from the others, which requires industry-specific solutions to the problems of digitalization and sustainability. Companies that invest time in the continuous education of their employees and align themselves to needs of the sector to be in are well placed in achieving sectoral competitive advantages and environmental objectives. The study also underlines the necessity of continuing the further research of human capital, digitalization, and sustainability concerns in supply chain relationships, particularly, considering the development of new technologies and customers’ changing preferences. Keywords: Supply chain, human capital, human capital management, sustainability, digital transformation, digitalization, digital literacy, employee engagement.